Vertically Aligned Graphene for Thermal Interface Materials. Issue 3 (13th September 2020) - Xu, Shichen; Zhang, Jin
Abstract : With the rapidly increasing power density and integration level in electronic devices, the development of the next generation of thermal interface materials (TIMs) with substantially high thermal conductivity is essential for various device technologies. Graphene, exhibiting ultrahigh in‐plane thermal conductivity, is investigated intensely for improving the heat dissipation performance. To satisfy the requirements of high vertical thermal conductivity of TIMs, numerous efforts have been made toward the development of the assembly method of graphene sheets extending the intrinsic properties of graphene to macro graphene‐based TIMs. A successful approach that erects graphene sheets to construct a vertical structure of graphene material has been widely demonstrated to significantly increase the thermal conductivity of graphene‐based TIMs. In this review, the latest advances in the rational design and controllable fabrication of vertical graphene structures by means of top‐down and bottom‐up methods are summarized. Moreover, the state‐of‐the‐art progress on graphene‐based TIMs is discussed from the viewpoint of material fabrication, structure design, and property optimization. Finally, the existing advantages, challenges, and perspectives of high‐thermal‐conductivity graphene‐based TIMs are presented and highlighted. Abstract : Herein, the latest advances in the rational design and controllable fabrication of vertical graphene structure–based thermal interface materials are presented. The approaches that erect graphene sheets to construct a vertical graphene structure are mainly classified into top‐down and bottom‐up methods, based on which the detailed synthesis strategies, related mechanisms, limiting factors, and optimized properties are summarized.